Revisiting of Karbala Through the Pages of Raghunath Choudhary - Wahidul Islam; Abul Kalam Choudhury (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In this article efforts have been made to revisit the Karbala poem of Raghunath Choudhary analyzing its literary view, elegy and tragedy, political consequences and human rights violation. Moreover, I have tried to introduce briefly about the writer of the poetry book, the characters and personalities mentioned in the poems. The tragedy of Karbala was an unfortunate incident that took place in 61 AH yet it is still fresh in the minds of the Muslims and affected Muslims deeply. Indeed, there have been extra-historical folklore and myth about the story of Karbala and Hasan-Hussain have been running in the Muslim society for a long time. Many poems, stories, plays, etc. have also been written on that incident since the tragedy happened. Although there is a same shadow of history in these narratives but the body is almost different. Some unsubstantiated information of the history is also included in his poems but the core and most of the events are purely factual. It is acknowledged that History and poetry are not the same things. Poetry is undoubtedly blossomed from the poet's imagination. The poet Raghunath Choudhary's